Recent Advances in the Synthesis and Application of C-2-Formyl Glycals - Arora, Aditi; Kumar, Sumit; Khatri, Vinod; Prasad, Ashok K.; Chhatwal, Rajni Johar; Kumar, Sandeep (Synthesis, 2023)
C-2-Formyl glycals have sustained interest in carbohydrate chemistry as they afford valuable chiral building blocks for many biological-, pharmaceutical-, and industrial-based important molecules. Basically, C-2-formyl glycals are a class of carbohydrates incorporating an α,β-unsaturated aldehyde. Therefore in many organic reactions, the C-2-formyl glycals can serve as an α,β-unsaturated aldehyde core. In this review, we have compiled a literature survey covering the period 2013–2022, on the synthesis of C-2-formyl glycals and further discuss their importance for the synthesis of many medicinal, supramolecular, biological, organic, and material chemistry based molecules.1 Introduction2 Synthesis of C-2-Formyl Glycals2.1 Vilsmeier–Haack Formylation2.2 By Consecutive Cyclization2.3 XtalFluor‑E Based Synthesis3 Applications of C-2-Formyl Glycals3.1 C-2-Formyl Glycals as a Synthons3.2 Anticancer3.3 Anti-inflammatory3.4 Antimicrobial3.5 Glycosidase Inhibitors3.6 Miscellaneous4 Conclusion and Future Aspects
Keywords: C-2-formyl glycals; α,β-unsaturated aldehyde; carbohydrate; Vilsmeier–Haack reaction; biological activity; glycosides